Evaluative organization of self-knowledge: The hidden vulnerability of compartmentalization. - Zeigler-hill, Virgil. (My University, 2004)
Three studies explored the possibility that the structure of the self-concept is associated with fragile self-esteem. The model of self-concept structure examined in the present studies is evaluative organization, especially the distinction between compartmentalization and integration. Compartmentalization is the tendency to segregate positively and negatively valenced self-beliefs into separate self-aspects, whereas integration is the tendency for attributes of opposite valence to appear in the same self-aspects. Study 1 showed that compartmentalization was associated with state self-esteem that was less stable over time and that appeared to be more reactive to daily events and stress. Study 2 found that the state self-esteem of compartmentalized individuals appeared to be primarily reactive to social events and that the self-esteem of these individuals was contingent upon meeting certain standards (e.g., approval of others and physical appearance). Study 3 employed a laboratory manipulation of social rejection to confirm that the state self-esteem of compartmentalized individuals was highly reactive to social rejection. Findings across the three studies suggest that individuals with compartmentalized self-concept structures may be best characterized as possessing fragile self-esteem, whereas individuals with integrative self-concepts appear to possess self-esteem that is relatively secure. These results suggest that some of the benefits believed to be associated with compartmentalization (e.g., high self-esteem) may actually reflect defensive processes rather than true psychological adjustment.
Keywords: Psychology, Personality.; Psychology, Social.; Self-perception.; Self-esteem.